Determinants of Chinese SMEs’ Entry to ASEAN Renewable Energy Market - W Luo; S. N. Jansri; W Rakwichian; W Setthapun (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2019)
ASEAN communities seek such resources as technologies and products from other countries to develop solar energy for sustainable development. In response to that, major renewable-utilization advanced countries including China has introduced funds, technology, and products into ASEAN. Despite the fact that China SMEs have a strong willingness to enter ASEAN solar energy market and ASEAN has demanded to develop the solar energy industry, only a few of them have succeeded in operation in the long-run. Introducing renewable energy technology and products from one place to another or bringing them from laboratory into community is not just a process of capital equipment supply from one firm to another but also includes the transfer of skills and know-how for operating and maintaining technology hardware, and knowledge for understanding this technology so that further independent innovation is possible by recipient. The purpose of this research was to determine the dynamic elements for China SMEs entering into the solar energy market of middle-income ASEAN member states. This participatory research collects data from both primary and secondary sources. Primary data sources include a questionnaire for 408 respondents of whom background across government officials, research personnel and industry, and interviews for 24 of them. Secondary data include reports from the Asian Development Bank, ASEAN Centre for Energy and other related documents from ASEAN governments. Data collected from the questionnaire were firstly analyzed through quantitative way: the value of Mean, Standard Error of Mean, Median, Standard Deviation (Std.) and Variance of each element were calculated. Information collected from interviews were then analyzed through the qualitative way. The results showed that policy environment, level of industrial and economic development, people’s willingness to cooperate, correct policy interpretation, capacity building and the presence of a third-party intermediary agency are the determinants of Chinese SME's successful entry to ASEAN renewable energy market. The mature policy environment of the ASEAN, need of industrial upgrading and sound economic development would facilitate the development of renewable energy industry, meanwhile, the strong willingness to cooperate, correct policy interpretation on preferential policies, well capacity building of both cooperative sides and the presence of a third-party intermediary agency would promote the cooperation between Chinese SMEs and relevant partners of ASEAN and the sustainable operation of Chinese SMEs in ASEAN.